Processing and microstructure-permeation properties of silica bonded silicon carbide ceramic membrane. Issue 15 (December 2021) - Li, Yang; Ma, Yanfei; Li, Yongsheng; Li, Shuang
Abstract: Porous SiC is a valuable membrane material for the microfiltration and ultrafiltration of various wastewaters because of its high hydrophilicity and low fouling tendency, but its preparation has been limited by the high sintering temperature. Here, a silica bonded silicon carbide membrane was prepared by the oxidation of SiC at low temperature. When the SiC substrates were sintered in the temperature range from 1200 to 1400℃, their porosity decreased from 45 % to 37 % while the flexural strength increased from 45 to 59 MPa. For the selective layers made from SiC particles with 0.5 μm in diameter, the average pore sizes that sintered at 1050 and 1150 ℃ were 0.34 and 0.26 μm, respectively, corresponding to the water fluxes of 1080 and 1240 L/(m 2 h, respectively. Thus, this technique provided a cost-effective path to prepare ceramic membrane at low sintering temperature.